Imperial estates in Roman Numidia : History, Exploitation and administration - bagar, Oussama (The Algerian Historical Journal, 2026)
Studying land ownership and its legal status in Numidia during the Roman period will discover that there were several different types: state lands, city lands, as well as imperial lands. In light of this, this article will attempt to present the historical process of the emergence and development of imperial properties in the northern and southern Numidian domain, and how the increase in their size prompted the emperors to introduce a set of administrative measures aimed at managing them more effectively. Then we try to determine the locations of the spread of these imperial properties across Numidian territory and the mechanisms for exploiting them. Let us conclude the study by presenting the administrative staff assigned to manage it, which we note was not only composed of official and equestrians, but also of freedmen and imperial slaves who played an important role in the management of districts of “Theveste” and “Hippo Regius” and were spread throughout many imperial property.